Allen Tate and His Work : Critical Evaluations - Squires, Radcliffe (Book collections on Project MUSE., 1972)
The thirty-five essays and memoirs about Allen Tate which are collected in this volume along with the introduction by Radcliffe Squires provide a perceptive, many-windowed view of Tates work and his life. Poet, critic, novelist -- Tate is all of these.